2017
DOI: 10.1038/nrclinonc.2017.195
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic profiling refines the molecular view

Abstract: Standfirst |Muscle-invasive bladder cancer (MIBC) is a heterogeneous disease for which treatment has, historically, lagged behind that of many other solid tumour types. A more detailed understanding of the biology of individual tumours and the identification of molecular features that provide prognostic and predictive information is key to the application of personalized care for patients with this disease. The recent publication of the complete TCGA study of 412 MIBC samples 1 now provides such data. Estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…TCGA data have provided the comprehensive molecular characterization of MIBCs [ 13 ]; however, the generated results need to be carefully evaluated. TCGA data revealed 58 significantly mutated genes and high frequencies of occurrence of several genetic pathways; however, given the heterogenic nature of MIBCs, the examination of even larger samples is essential to obtain a complete catalogue of mutations or pathways, including those with low frequencies [ 32 ]. Creating a reasonably comprehensive catalogue of candidate cancer genes mutated in ≥2% of patients with MIBCs will require thousands of samples, given the high overall mutation rates of these cancers [ 33 ].…”
Section: Molecular Biomarkers and Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…TCGA data have provided the comprehensive molecular characterization of MIBCs [ 13 ]; however, the generated results need to be carefully evaluated. TCGA data revealed 58 significantly mutated genes and high frequencies of occurrence of several genetic pathways; however, given the heterogenic nature of MIBCs, the examination of even larger samples is essential to obtain a complete catalogue of mutations or pathways, including those with low frequencies [ 32 ]. Creating a reasonably comprehensive catalogue of candidate cancer genes mutated in ≥2% of patients with MIBCs will require thousands of samples, given the high overall mutation rates of these cancers [ 33 ].…”
Section: Molecular Biomarkers and Pathwaysmentioning
confidence: 99%
“…Creating a reasonably comprehensive catalogue of candidate cancer genes mutated in ≥2% of patients with MIBCs will require thousands of samples, given the high overall mutation rates of these cancers [ 33 ]. Considering the reduced costs of sequencing, a more comprehensive catalogue of MIBCs is likely to be generated in the near future [ 32 ]. Further, almost no studies have replicated the results of the TCGA study [ 13 ]; therefore, it is important that the results be confirmed by other cohorts.…”
Section: Molecular Biomarkers and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Bladder cancer is the sixth most common cancer in male patients and has a global incidence of over 400,000 new cases per year, with 165,000 bladder-cancer-related deaths each year 1, 2. After bladder cancer progresses to the advanced stage, the only option for treatment is cisplatin-combined chemotherapy 3.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer is the most common form of urinary tract cancer, leading to >165,000 succumbing to the tumor every year worldwide (5,6). Bladder cancer is a heterogeneous disease with a poor prognosis, indicating the tremendous challenge that the treatment of this disease proposes.…”
Section: Introductionmentioning
confidence: 99%